Correlation Between Noise Levels and Noise-Induced Hearing Loss in Ground Handling Officers at Kualanamu Airport - Putra, Aldi Maulana; Herwanto, Yusa; Lubis, Yuliani M.; Ashar, Taufik (Jurnal Biologi Tropis, 2025)
Airport ground handling officers are highly exposed to noise from aircraft operations, potentially leading to Noise-Induced Hearing Loss (NIHL). This study aims to investigate the correlation between noise levels and NIHL among ground handling officers at Kualanamu Airport. A cross-sectional observational design was applied. Data on noise levels were obtained using a sound level meter, and NIHL was assessed with a calibrated Interacoustics audiometer AD528. Among 23 officers exposed to 95 dB, 16 (69.6%) had NIHL, and among 5 officers exposed to 100 dB, 4 (80%) had NIHL. Statistical analysis using the Kruskal-Wallis test confirmed a significant relationship between noise levels and NIHL (p<0.001). The study highlights the need for preventive strategies in noisy airport environments. The conclusion is that there is a significant correlation between occupational noise exposure and the incidence of Noise Induced Hearing Loss (NIHL) among ground handling officers at Kualanamu International Airport.